2022
DOI: 10.3390/ijms231911245
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota–Gut–Brain Axis in Psychiatric Disorders

Abstract: Modulating the gut microbiome and its influence on human health is the subject of intense research. The gut microbiota could be associated not only with gastroenterological diseases but also with psychiatric disorders. The importance of factors such as stress, mode of delivery, the role of probiotics, circadian clock system, diet, and occupational and environmental exposure in the relationship between the gut microbiota and brain function through bidirectional communication, described as “the microbiome–gut–br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(80 citation statements)
references
References 183 publications
0
49
0
2
Order By: Relevance
“…Recently, there is growing interest in the other serious consequences of gut microbiota imbalance. Gut dysbiosis impairs the function of the gut–brain axis, which is associated with the development of various neurological and psychiatric disorders such as anxiety, stress, major depressive disorder, schizophrenia, bipolar disorder, autism spectrum disorder, and attention-deficit hyperactivity disorder, as well as Parkinson’s disease, Alzheimer’s disease, dementia, multiple sclerosis, and epilepsy [ 267 , 268 , 269 , 270 , 271 ].…”
Section: Possibility Of the Intestinal Microbiota Inhibition And Cons...mentioning
confidence: 99%
“…Recently, there is growing interest in the other serious consequences of gut microbiota imbalance. Gut dysbiosis impairs the function of the gut–brain axis, which is associated with the development of various neurological and psychiatric disorders such as anxiety, stress, major depressive disorder, schizophrenia, bipolar disorder, autism spectrum disorder, and attention-deficit hyperactivity disorder, as well as Parkinson’s disease, Alzheimer’s disease, dementia, multiple sclerosis, and epilepsy [ 267 , 268 , 269 , 270 , 271 ].…”
Section: Possibility Of the Intestinal Microbiota Inhibition And Cons...mentioning
confidence: 99%
“…The microbiome is important for the immune system, brain and genome. A series of recent studies have demonstrated that the microbiome influences the central nervous system in multiple ways and influences the psychological state of individuals by mediating reactions to stress and anxiety (26)(27)(28)(29)(30). The enteric nervous system (ENS), composed of two layers of approximately 100 million nerve cells that line the digestive tract from the oesophagus to the rectum, is an independent centre for neural processing and integration.…”
Section: Figure 1 Direct and Indirect Mechanisms Of Bacteria Infectin...mentioning
confidence: 99%
“…A balanced and appropriate composition of the gut microbiota confers health benefits; a disruption of this balance can reflect on brain function and behavior by acting through the microbiome–gut–brain axis [ 46 ], our “second brain” [ 45 ]. The relative abundance of the single species constituting the microbiota and its metabolites are associated with the onset of neurologic and psychiatric disorders [ 75 ]. GI disorders (ranging from severe constipation to diarrhea) are frequently observed in individuals with ASD; however, they are estimated to occur with a wide variability, from 2.2% to 96.8% of the ASD population [ 76 ].…”
Section: Ndd-associated Gastrointestinal Symptomsmentioning
confidence: 99%